Representações sociais de mães sobre estimulantes de apetite em crianças - Ramos, Diego Carneiro (2014)
Introduction: Nutrition goes beyond the physiological need. Nutrition is part of a symbolic universe that gives different meanings to food and nurturing. Among the maternal responsibilities, the nutrition occupies a special place in care. This maternal task makes the mothers feel apprehensive when the children do not reach the expectations of nutrition they have, either rejecting or selecting foods too eat and what to eat. These factors combined with the relationship between child health and corporeality makes mothers seek for drugs that can intervene in appetite or weight children. Objective: This study aims to ascertain the reasons mothers manage appetite stimulants to children and what senses are involved in this act of care. Methodology: The object of this study pointed to the necessity of using methodological principles of qualitative research. The theory of Social representations was used as theoretical support. The study was conducted through semi - structured interviews with 15 mothers living in a neighbourhood in Conceição do Coité (Bahia). The selected mothers should have administered drugs to stimulate appetite in their under five years old children or have related any general use of stimulant medications appetite. Data were analysed based on the technique of content analysis. Results: These medicines were used for various purposes. The main reason was to increase the amount of food eaten. To direct interest of the child to foods that mothers understand are better was another reason , along with the desire that the child gain more weight and eat at set times. To provoke disinterest in breast milk and cause sedation in children were other findings. The use of these medicines often occurred as a self-medication, stimulated and guided by nearby people and other mothers who have made the same practice. Conclusion: This research reveals a variety of reasons for the use of medicines, regulated by social representations that mothers do appetite, eating habits of the children and the pharmaceutical product classified as an appetite stimulant.